Nicaragua : Fourth and Fifth Review Under the Three-Year Arrangement Under the Extended Credit Facility, Requests for Extension of the Arrangement, Rephasing of Access, and Waiver of Nonobservance of Performance of Criterion, and Financing Assurances Review-Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Nicaragua. (IMF Staff Country Reports; Country Report ;, 2010)
Economic performance in Nicaragua has been better than envisaged; nonetheless, vulnerabilities remain and will be compounded by electoral uncertainties. The decision to use part of the strong revenue performance to lower the fiscal deficit is appropriate. Exchange-rate and monetary policy remain broadly adequate. Fiscal adjustment should set the stage for a strong program of fiscal consolidation following the elections. Continued vigilance in the financial sector will be critical. Improvement in reporting and monitoring of foreign aid flows and transparency is necessary.